Sherpany: should I stay or should I go; successful IT nearshoring of a tech startup - Guggenbuehl, Caspar Heinrich Paul (2022)
The sun slowly sinks into the Atlantic Ocean, casting its last golden rays onto the aggressively breaking waves below the Cabo da Roca. Their fury and power is not lost on Tobias Häckermann, the CEO of Sherpany. The idyllic scene in front of him has come to symbolize his Portuguese adventure - beautiful and rewarding. The Swiss CEO paused in the striking sunset for a moment of reflection. The events of the last year (2014) had been remarkable. Sherpany, his invention and a technology company providing solutions for boardroom communication, was gaining traction. Sales were now in the millions of Euros.1 Demand for services was high and the future was bright. This success story is not the result of just good fortune but rather the culmination of many strategic milestones. Häckermann’s hometown of Zurich (Switzerland) is one of the most expensive cities in the world (see Exhibit 1). It was impossible to enlist IT talent and exorbitant fixed operating costs threatened the viability of his business model. In short, Sherpany faced the classic “valley of death” scenario2a that every startup must overcome. In Häckermann’s case, the need for a fast and cost-effective way to securely grow the company and keep ahead of the competition forced him to nearshore a significant part of his operations - to Portugal. In hindsight, it all seemed so logical: a short flight from Zurich, great weather, 1-hour time difference, lower costs of labour, and abundant local IT talent looking for international opportunities, and all under the security blanket of the EU.